2017
DOI: 10.3892/mmr.2017.7955
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of TRIM28 inhibits growth and increases apoptosis of nude mice with non‑small cell lung cancer xenografts

Abstract: TRIM28 is a well-known transcriptional co-repressor of Kruppel-associated box zinc finger proteins. The authors previously demonstrated that TRIM28 small interfering (si)RNA decreases cell proliferation and inhibits cell cycle progression in non-small cell lung cancer (NSCLC) cell lines. The present study further demonstrated that the stable silencing of TRIM28 expression by a specific siRNA lentivirus vector significantly inhibited the growth and exerted obvious anti-tumor effects in nude mice. The results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Here, we show that during differentiation of iPSC due to TRIM28 depletion, there is a significant shift in cellular signaling. We demonstrate that silencing TRIM28 leads to upregulation of processes related to the regulation of apoptosis, differentiation into a multicellular organism, positive regulation of the developmental process, and regulation of the cell cycle, which is also confirmed by earlier evidence [9,74,75].…”
Section: Discussionsupporting
confidence: 86%
“…Here, we show that during differentiation of iPSC due to TRIM28 depletion, there is a significant shift in cellular signaling. We demonstrate that silencing TRIM28 leads to upregulation of processes related to the regulation of apoptosis, differentiation into a multicellular organism, positive regulation of the developmental process, and regulation of the cell cycle, which is also confirmed by earlier evidence [9,74,75].…”
Section: Discussionsupporting
confidence: 86%
“…Previous reports showed that 30%-35% stage I NSCLC patients treated with surgery may progress to local recurrence or distant metastasis within five years [ 4 ]. The 5-year survival rate is 83.9% in stage IA and 66.3% in stage IB NSCLC [ 5 ]. Lung adenocarcinoma (LUAD) is the most common histologic type of NSCLC with morbidity and mortality persistently elevated over past decades [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…They believed that TRIM28 played a pivotal role in cervical cancer cell proliferation and might serve as a potential therapeutic target. In non-small cell lung cancer (NSCLC) cell lines, Liu L [9] demonstrated that the stable silencing of TRIM28 expression by a specific siRNA lentivirus vector significantly inhibited the growth and exerted obvious anti-tumor effects in nude mice. Furthermore, TRIM28 expression was significantly correlated with several clinicopathological characteristics of patients with breast cancer (BC), such as p53 mutation, tumor recurrence and Elston grade of the tumor [11].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the evolutionarily conserved TRIM family proteins, TRIM28 has been proved to accelerate cell proliferation and metastasis in a variety of human cancers. Studies have shown, for example, that TRIM28 knockdown may be effective against NSCLC, and the knockdown of TRIM28 expression by lenti-siRNA/TRIM28 may inhibit tumor growth and induce cell apoptosis in vivo [9, 10]. Hao L found that TRIM28 is frequently elevated in multiple tumor types and is associated with aggressive clinical features of breast cancer.…”
Section: Introductionmentioning
confidence: 99%